PREDICTORS OF INTENTION TO USE FUNCTIONAL APPLICATIONS FOR MOBILE HEALTH IN THE REPUBLIC OF SERBIA USING THE EXPANDED UTAUT2 METHOD - Mijić, Miloš; Ćebić, Branko; Bogdanović Vasić, Slobodanka (HEALTH CARE, 2025)
Introduction/Aim: Health mobile applications provide an opportunity for each user to proactively monitor and manage their health. The mHealth mobile application uses the latest technology with the aim of making healthcare more accessible and affordable to more users. The aim of this paper was to identify factors, defined according to the expanded UTAUT2 (Unified Theory of Acceptance and Use of Technology) model, which have an impact on the intention to use mobile health applications (mHealth) in the Republic of Serbia. Methods: The cross-sectional study included 64 respondents (opportunity sample), former students, teachers and associates of the Academy of Vocational Studies in Western Serbia, who filled out an online questionnaire in the period May - November 2024. Cronbach’s coefficient α, Pearson correlation coefficient and regression analysis were used in the data analysis. Results: Five of the 7 elements (Performance Expectancy - PE, Effort Expectancy - EE, Social Influence - SI, Price Value - PV and Facilitating Conditions - FC) of the UTAUT2 model are significant predictors of respondents’ intention to accept and use mHealth mobile application services. Habit (H) elements and hedonic motivation (HM) have no significant effect on the use of mHealth mobile applications. Correlation analysis indicates that behavioral intention (BI) correlates significantly strongly positively with EE, facilitating conditions - FC and PE, and significantly positively but weakly with SI and PV. No significant correlation was found with HM and H. Conclusion: Further research in this area is necessary, especially research related to the testing and use of a specific mobile application for mHealth according to the elements of the UTAUT2 model.